2015
DOI: 10.1002/ange.201411403
|View full text |Cite
|
Sign up to set email alerts
|

Direct C(sp2)C(sp3) Cross‐Coupling of Diaryl Zinc Reagents with Benzylic, Primary, Secondary, and Tertiary Alkyl Halides

Abstract: The direct C(sp 2 ) À C(sp 3 )c ross-coupling of diaryl zinc reagents with benzylic,p rimary,s econdary,a nd tertiary alkylhalides proceeded in the absence of coordinating ethereal solvents at ambient temperature without the addition of acatalyst. The C(sp 2 )ÀC(sp 3 )cross-coupling showed excellent functional-group tolerance,and products were isolated in high yields,g enerally without the requirement for purification by chromatography.This process represents an expedient, operationally simple method for the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…We note that iron is essential for activity, precluding the possibility that catalysis proceeds via a zinc-mediated process. 58 Furthermore, a comparison of reactivity under conditions that allow the zinc-mediated process in both the presence and absence of dpbz showed that the diphosphine retards the rate (Supplementary Figure 162). What then is the role of the phosphine?…”
Section: Phosphine-zinc Speciesmentioning
confidence: 99%
“…We note that iron is essential for activity, precluding the possibility that catalysis proceeds via a zinc-mediated process. 58 Furthermore, a comparison of reactivity under conditions that allow the zinc-mediated process in both the presence and absence of dpbz showed that the diphosphine retards the rate (Supplementary Figure 162). What then is the role of the phosphine?…”
Section: Phosphine-zinc Speciesmentioning
confidence: 99%